Conditional Cash Transfers in Resource-poor Environments: Evidence from the Philippine 4Ps - Michael Ralph M. Abrigo; Danika Astilla-Magoncia; Zhandra C. Tam; Sherryl A. Yee (Philippine Institute for Development Studies (PIDS), 2022)
We provide new evidence of the heterogeneous impact of the Philippines' conditional cash transfer (CCT) program designed to improve human capital investments among children from poor households. Using a regression discontinuity design, our moderation analysis shows that the distance to and quality of education and health facilities matter in child schooling and vaccination behaviors. Conditional cash transfers provide some but incomplete protective effects against the adverse influence of suboptimal facility conditions on these child outcomes. We also document no crowding out effects from some elective affirmative actions directed towards CCT beneficiaries.
Keywords: 330; conditional cash transfer; 4Ps; education; health; impact evaluation